Development, characterization and analysis of auxetic structures from braided composites and study the influence of material and structural parameters. (August 2016) - Magalhaes, Rui; Subramani, P.; Lisner, Tomas; Rana, Sohel; Ghiassi, Bahman; Fangueiro, Raul; Oliveira, Daniel V.; Lourenco, Paulo B.
Abstract: Auxetic materials are gaining special interest in technical sectors due to their attractive mechanical behaviour. This paper reports a systematic investigation on missing rib design based auxetic structures produced from braided composites for civil engineering applications. The influence of various structural and material parameters on auxetic and mechanical properties was thoroughly investigated. The basic structures were also modified with straight longitudinal rods to enhance their strengthening potential in structural elements. Additionally, a new analytical model was proposed to predict Poisson's ratio through a semi empirical approach. Auxetic and tensile behaviours were also predicted using finite element analysis. The auxetic and tensile behaviours were observed to be more strongly dependent on their structural parameters than the material parameters. The developed analytical models could well predict the auxetic behaviour of these structures except at very low or high strains. Good agreement was also observed between the experimental results and numerical analysis.